The educational and parenting test for home-based childcare: a socially valid self-rating instrument - Baumeister, Antonia Elisabeth Enikoe; Jacobsen, Julia; Rindermann, Heiner (Frontiers in Education, 2023)
Introduction Home-based childcare is increasingly becoming the focus of research, policy and public interest. Self-assessment of quality can increase the social validity of quality improvement efforts among stakeholders. A new online self-assessment tool for parents and non-relative providers of home-based childcare is introduced that has been developed in Germany, the Educational and Parenting Test for Home-Based Childcare (EPT; in German: ‚Bildungs- und Erziehungstest für TagesElternBetreuung BET‘). Methods In two studies, the social validity of the EPT was investigated: a stakeholder study with 45 parents and 12 non-relative caregivers, and an expert study with nine experts of child pedagogy. The stakeholders rated the EPT survey (N = 57) and the subsequent report of test results (n = 22). The experts evaluated the survey and the feedback report based on vignettes of three fictitious test results (i.e., below average, average, and above average quality). Criteria included face validity, measurement quality, controllability (i.e., comprehensiveness), freedom of response, freedom of pressure, counseling quality, usefulness, control of bias, and privacy protection. Results Most aspects of social validity achieved good to very good ratings. All three samples graded the EPT survey as “good.” If the stakeholders felt that their educational quality was undervalued, they rated the report of test results worse (rs(20) = 0.52, p = 0.02). Five of seven experts would recommend the EPT to others. Discussion Based on participants’ comments, the instrument was thoroughly revised. The EPT is a socially valid instrument for assessing and developing quality in home-based childcare.